Fun Athletics: Optimizing The Sprint Running Potential of Elementary School Students Through A Game Approach - Suhariyanti, Mela; Guntur Yuli Satria; Yopi Hutomo Bakti; Nur Hikmah (Universitas PGRI Palembang, 2025)
This study was carried out to analyze the impact of the use of play methods in improving sprint running ability in students of SDN 2 Dono Arum, Central Lampung. The research uses a quasi experiment approach with a one-group pretest-posttest design. The subject of the study was a male student in grade IV of SD Negeri 2 Dono Arum, Central Lampung. Sample selection was carried out through a purposive sampling technique by taking 10 male students as participants. In data collection, the researcher used a sprint running test instrument with a distance of 60 meters. Data analysis was carried out using the paired t-test to compare the average value of pretest and posttest results before and after the treatment. Before conducting the paired t-test, the researcher first carried out a data normality test. Based on the results of the study, it was found that after applying the play method in practice, the average ability of students increased by 1,000 seconds. Thus, it can be concluded that the play method has an influence on the improvement of sprint running ability in grade IV male students of SD Negeri 2 Dono Arum, Central Lampung